Conclusion: Biological monitoring as a means to assess exposure and to predict adverse effects of chemical pollutants: an over view of current activities in key Italian laboratories - Mutti, Antonio (La Medicina del Lavoro, 2012)
Facilities and technologies are now available to explore the nanomolar range of xenobiotics in biological media. As a consequence of improved analytical capabilities, it is now possible to identify biomarkers useful to assess exposure to environmental contaminants and residual occupational exposure at workplaces where effective prevention measures have been taken. Such increased sensitivity and selectivity of analytical instruments relying on mass spectrometry is particularly suitable to assess exposure to carcinogenic agents, for which even trace amounts are regarded as contributing to overall risk of cancer. This is the reason why....